1995
DOI: 10.1148/radiology.195.3.7753999
|View full text |Cite
|
Sign up to set email alerts
|

Congenital ossification of the stapedius tendon: diagnosis with CT.

Abstract: At CT, a linear area of soft-tissue attenuation that extends from the pyramidal eminence to the monopod stapes is suggestive of congenital ossification of the stapedius tendon or a bony bar adjacent to it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…An ossified stapedius tendon can sometimes be visualised on a high-resolution CT scan. 6 In our case, a CT scan was not performed. We decided to perform an exploratory tympanotomy instead.…”
Section: Discussionmentioning
confidence: 79%
“…An ossified stapedius tendon can sometimes be visualised on a high-resolution CT scan. 6 In our case, a CT scan was not performed. We decided to perform an exploratory tympanotomy instead.…”
Section: Discussionmentioning
confidence: 79%
“…Stapedial tendon ossification can be diagnosed using preoperative CT and exploratory tympanotomy. On temporal bone CT, it can be diagnosed as a linear image from the pyramidal eminence to the stapes superstructure[ 7 ]. Based on these findings, it can be differentiated from otosclerosis[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, it can be diagnosed by computed tomography (CT) and tympanotomy. In addition, it is easily mistaken for otosclerosis, and thus discrimination is essential[ 7 ]. In the case described herein, surgical division was performed after diagnosing stapedial tendon ossification through exploratory tympanotomy, but hearing recovery was insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…2 Other common conditions resulting in stapes fixation should be considered in the differential diagnosis, including tympanosclerosis, fenestral otosclerosis, congenital stapes fixation, absence of the oval window, and a persistent stapedial artery. 3 The etiology of ossification of the stapedius tendon remains controversial. Hough indicated that the ossification of the stapedius tendon rarely resulted from congenital causes and that tympanosclerotic degeneration frequently induced complete immobility that resulted in stapes fixation.…”
Section: Kai-chieh Chan MDmentioning
confidence: 99%
“…2 Surgical treatment can be performed by the simple division of the ossified stapedius tendon, or by stapedotomy/stapedectomy in patients with associated fixation of the stapes footplate. 3 Congenital nonsyndromic ossicular anomalies are an uncommon cause of conductive hearing loss. Of these, stapes fixation caused by an ossified stapedius tendon with normal mobility of the footplate, although rare, should be included in the differential diagnosis of conductive hearing loss with a normal tympanic membrane.…”
Section: Kai-chieh Chan MDmentioning
confidence: 99%